Designing for/in the inclusive school - Montanari, Mirca; Persi, Rosella (Journal of Education For Sustainable Innovation, 2024)
The quality of inclusive education is, now more than ever in the post-pandemic historical phase, closely connected to the constant and profound renewal and transformative readjustment of design practices in every school order and grade. Educational design for all, for pupils with and without special educational needs, is an effective teaching tool that facilitates participation and reduces barriers to learning based on the framework provided by the main inclusive models (ICF, Universal Design for Learning). In identifying and attempting to remove the obstacles that may be generated within it, schools tend to embrace and promote a strong design culture that is attentive to the needs of all, committed to making a fertile contribution to the development of educational policies in the name of enhancing and interpreting the heterogeneity of differences in the classroom. In this perspective, several good inclusive school practices are examples of personalized and individualized teaching activities that, undertaken and implemented in concrete day-to-day operations, have a systemic impact on educational pathways without excluding anyone.